Frustacionit and Crime in Contemporary Society - Case Study the Western Balkan - Qollkaj, Fatmir (European Journal of Social Science Education and Research, 2022)
When we talk about society, in particular in terms of developing its sociological us always remains good impression when talking to a healthy society and developed, however long history of social development gives us to understand that the development of society is also followed by numerous pathological phenomenon, deviant and criminal. This phenomenon, as the development of regression contradictions are development testified as a driving force of society, not just the dialectical point of view worldly but also from the standpoint of Merton Dyrkemit of other thinkers of the twentieth century. Criminality as a result of the promoters, different forces the drive has been the phenomenon of early and ongoing follow-up of human society, caused in most of the time the frustrations such as individual and collective. Starting from the individual, then the family, group and to greater social organization, frustrations are manifest modalities of development as controversial complex, multidimensional social. Changes occurring in contemporary society in the late twentieth century terms as in terms development economic, technical and technological followed with profound changes in the political, legal and cultural.These changes greatly influenced the lives of states social training, companies involved in this global development where ragging result of increased individual and collective result of which is also the growing crime in intensity and modalities manifest.